Exploring Life-Centered Design through a bottom-up analysis of case studies - Niccolò Casiddu; Claudia Porfirione; Francesco Burlando; Annapaola Vacanti; Isabella Nevoso (Techne, 2025)
This paper explores Life-Centred Design (LCD), an emerging concept aiming to overcome anthropocentric approaches by addressingall forms of life in the design process. Through a bottom-up analysis of case studies, it identifies the distinctive traits of LCD compared to other post-human approaches. The findings highlight the strong integration of foundational LCD principles, such as sustainability and systemic thinking, while revealing challenges in implementing co-design practices, non-human agency, and prioritising non-human interests. Addressing these complexities is essential for advancing LCD into a practical framework capable of tackling Anthropocene challenges.